2010
DOI: 10.1097/psy.0b013e3181ec4b98
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Race, and Circulating C-Reactive Protein: The Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: Objective-To examine the prospective association of depressive symptoms with circulating Creactive protein (CRP) and determine the direction of that association.Methods-Using data from 2544 healthy participants in the Coronary Artery Risk Development in Young Adults (CARDIA) study (ages 33-45, 55% female, 42% black), we examined the prospective association of depressive symptoms, as measured by the Centers for Epidemiologic Studies Depression Scale (CES-D), with circulating CRP five years later.Results-Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 45 publications
5
56
3
Order By: Relevance
“…In contrast, average IL-6 levels only varied by 0.01–0.11 pg/mL among the top 3 quartiles. Thus, consistent with past research (12), lack of positivity appears to be particularly important for inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, average IL-6 levels only varied by 0.01–0.11 pg/mL among the top 3 quartiles. Thus, consistent with past research (12), lack of positivity appears to be particularly important for inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…For example, trait positive affect, but not negative affect, has been linked to lower production of stimulated cytokines in a middle-aged community sample (16). Prospective data from a large cohort of healthy adults showed that, among Black participants, low positive affect uniquely predicted higher CRP five years later but depressive affect did not (12). …”
Section: Introductionmentioning
confidence: 99%
“…21 Indeed, these symptom clusters have been shown to have differential impact on HF outcomes 22, 23 as well as other indices of cardiovascular function. 2429 For example, some studies found that the somatic symptoms cluster (e.g., sleep disturbance, appetite changes, and low energy) was the strongest predictor across a variety of outcomes, 22, 25, 29 whereas other studies reported similar results for the nonsomatic symptom clusters (e.g., cognitive, affective, or behavioral symptoms). 23, 2628 For example, Schiffer et al 22 found that individuals with high somatic symptom scores had a greater incidence of mortality than those with low scores (31% vs. 15%; hazard ratio = 2.3).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cross-sectional studies show that pro-inflammatory cytokines and C-reactive protein (CRP) are elevated among depressed individuals and among those who experienced early adversity (Dowlati et al, 2010; Haapakoski et al, 2015; Howren et al, 2009; Lacey et al, 2014; Liu et al, 2012; Matthews et al, 2014; Taylor et al, 2006). Prospective studies have similarly shown that exposure to early adversity or to clinical and subclinical levels of depression predict higher levels of subsequent inflammation (Copeland et al, 2012, 2014; Danese et al, 2007; Deverts et al, 2010; Matthews et al, 2010; Slopen et al, 2013). …”
Section: Introductionmentioning
confidence: 99%